2019
DOI: 10.1093/nar/gkz378
|View full text |Cite
|
Sign up to set email alerts
|

Caver Web 1.0: identification of tunnels and channels in proteins and analysis of ligand transport

Abstract: Caver Web 1.0 is a web server for comprehensive analysis of protein tunnels and channels, and study of the ligands’ transport through these transport pathways. Caver Web is the first interactive tool allowing both the analyses within a single graphical user interface. The server is built on top of the abundantly used tunnel detection tool Caver 3.02 and CaverDock 1.0 enabling the study of the ligand transport. The program is easy-to-use as the only required inputs are a protein structure for a tunnel identific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
174
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(175 citation statements)
references
References 54 publications
1
174
0
Order By: Relevance
“…The main wider tunnel has an average tunnel length of 8.8 Å, its average bottleneck radius is 2.2 Å, and its average tunnel throughput is 0.90 (this parameter describes the probability that the pathway is used as a route for transport of the substances, maximal value is 1.0). The second tunnel has an average length of 15.2 Å, an average bottleneck radius of 1.4 Å, and an average tunnel throughput of 0.67 [34]. The output of CAVER 3.0 provided us with the necessary data for CAVERDOCK computational analysis of the time evolution of individual pathways.…”
Section: Anrut Structure and Description Of Substrate Tunnelsmentioning
confidence: 99%
“…The main wider tunnel has an average tunnel length of 8.8 Å, its average bottleneck radius is 2.2 Å, and its average tunnel throughput is 0.90 (this parameter describes the probability that the pathway is used as a route for transport of the substances, maximal value is 1.0). The second tunnel has an average length of 15.2 Å, an average bottleneck radius of 1.4 Å, and an average tunnel throughput of 0.67 [34]. The output of CAVER 3.0 provided us with the necessary data for CAVERDOCK computational analysis of the time evolution of individual pathways.…”
Section: Anrut Structure and Description Of Substrate Tunnelsmentioning
confidence: 99%
“…For probing the structure and function of sugar transporters on targeted carbon molecules, identification of tunnels is the next key step. In order to predict the theoretical position of xylose when binding with CCM_06358, Caver Web 1.0 [52] was used to predict a catalytic pocket located at the TM1 and TM2 (residues 38 to 69) with high druggability of 0.89 ( Figure 5B). The xylose at this opening position was docked, and the binding pose showed that the xylose interacted with Gln50, Met311, and Thr315 through H-bonds ( Figure S2A).…”
Section: Annotated Molecular Structure and Transport Pathway Of A Selmentioning
confidence: 99%
“…Then, the AutoDock 4.2.6 software was employed to predict the binding mode between HSF-1 and Sch A [22]. The binding site was predicted by Caver Web server, and covered by a grid box size of 22.5 × 22.5 × 22.5Å dimensions [23]. The globe conformational sampling was set to trials of 200 dockings, and settings were set as default.…”
Section: Molecular Dynamics Simulation Of the Complex Between Hsf-1 Amentioning
confidence: 99%